Farmers' Perception of Constraints in Adoption of Fodder Production Technologies in Bundelkhand Region of India - Suman, Manju; Kumar, Ashok; Kumar, Vikas (Indian Journal of Extension Education, 2017)
The constraints regarding adoption of fodder production technology were studied in Bundelkhand region. Total of 180  respondents were sampled from four districts of regions representing both Uttar Pradesh (UP) and Madhya Pradesh (MP)  Bundelkhand in the study. It was found that 84.1% of respondents expressed that small landholding among them was the  primary constraint for lesser adoption of fodder production technology in area. About 79 per cent of farmers identified  lack of irrigation as the second most important reason for less adoption of fodder technology. The main reason for less  Knowledge of fodder production technologies were lack of awareness about improved technologies followed by lack of  on-farm guidance/training, lack of lesser resources and lesser literacy among them. The correlation between knowledge  gap and adoption gap was highly significant and positive.
Keywords: Farmers perception; adoption gap; knowledge gap; bundelkhand; fodder production technology